PENGUKURAN ZAT WARNA Monascus purpureus MENGGUNAKAN LCMS - Yuliana, Anna (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2020)
The formation of Monascus purpureus color-substance, as the result of solid fermentation, had been studied by using IR64 rice as a substrate. The formation of color substance had been measured by extracting the sample using 80% methanol which had undergone 14-day fermentation, followed by the thin-layer chromatography (TLC) test with the eluent of chloroform: methanol: water (90: 25: 4). The thorough test was accomplished by using UV-Vis spectrophotometry. The absorbance of Monascus purpureus color substance was measured by UV-Vis spectrophotometry at 364, 365, 375, 400, 480 and 500 nm wavelength. The results of color pigment absorbance of each isolate variedly were in the range of 0.219-0.590. The following analysis was done by using Liquid Chromatography-Mass Spectrum (LC-MS). LC-MS results showed the differences of each isolate. The IPB-B and IPB-T isolates showed that there were two compounds identified to have 359 and 386 molecular weight, ITBCC isolates showed that there were three compounds identified to have 359 371 and 386 molecular weight, while INACC F01 and INACC F147 isolates showed that there were five compounds identified to have 294, 346, 359, 371 and 386 molecular weight. The study result showed that the differences of isolate affect the production of Monascus purpureus color substance.